2018
DOI: 10.1093/europace/euy220
|View full text |Cite|
|
Sign up to set email alerts
|

Performance of idarucizumab as antidote of dabigatran in daily clinical practice

Abstract: Because practice-based data on the usage of idarucizumab for urgent dabigatran reversal is unavailable, we evaluated the appropriateness of idarucizumab usage, its haemostatic effectiveness and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
25
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 20 publications
2
25
1
1
Order By: Relevance
“…In nearly half of patients (48%), idarucizumab was administered prior to acute surgery and in 43% because of bleeding. These findings differ from those reported in a Dutch study of real-world use of idarucizumab in 88 consecutive patients between 2016 and 2018 [14]. In the Dutch cohort, 60% had severe bleeding as indication for treatment.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In nearly half of patients (48%), idarucizumab was administered prior to acute surgery and in 43% because of bleeding. These findings differ from those reported in a Dutch study of real-world use of idarucizumab in 88 consecutive patients between 2016 and 2018 [14]. In the Dutch cohort, 60% had severe bleeding as indication for treatment.…”
Section: Discussioncontrasting
confidence: 96%
“…From Montefiore Medical Center in New York, Goriacko et al reported clinical resolution of bleeding in six of seven cases and no adverse events [19]. Further, in the aforementioned Dutch study, they found that effective haemostasis was achieved in 74% of cases following idarucizumab use [14].…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, only small case series about idarucizumab use have been reported, [9][10][11] and a larger study of a cohort from 20 hospitals in the Netherlands analysed 88 patients (53 with severe bleeding and 35 requiring urgent surgical intervention). 12 Effective haemostasis was achieved in twothirds of bleeding patients and was associated with lower mortality risk. Clinical outcomes were considered similar to those observed in the RE-VERSE AD trial, regarding recurrent bleeding, thromboembolism and a high mortality rate.…”
mentioning
confidence: 99%
“…Indeed, using different definitions which were not possible to evaluate in the RE-VECTO, van der Wall et al found that the use of idarucizumab was inappropriate in 28% of patients, including a significant number of patients with interventions that could have been delayed or those with bleeding complications not considered uncontrollable. 12 Patients in the RE-VECTO surveillance program were rather poorly characterized regarding their baseline characteristics. While the main findings in the RE-VECTO report were broadly consistent to those observed in the RE-VERSE AD, the patient clinical profile in the RE-VECTO program might not be similar to that in the clinical trial, thus compromising the generalizability of the RE-VECTO findings.…”
mentioning
confidence: 99%
“…Что касается применения идаруцизумаба в реальной клинической практике, то в последние годы постепенно накапливается опыт его применения у больных как с продолжающимися кровотечениями [13,14], так и перед проведением оперативных вмешательств, в том числе у пациентов с острым повреждением почек [15,16]. Отдельно стоит отметить, что все чаще появляются сообщения об использовании идаруцизумаба для нейтрализации эффекта дабигатрана у больных, которым показано выполнение экстренной тромболитической терапии [17][18][19][20].…”
unclassified